2005
DOI: 10.1038/sj.jea.7500445
|View full text |Cite|
|
Sign up to set email alerts
|

Biomonitoring of chromium for residents of areas with a high density of electroplating factories

Abstract: The high density of electroplating factories in the geographic middle of Taiwan has prompted concern over the potential for exposure to harmful metals. The present study aimed to determine the levels of chromium in whole blood (B-Cr) of residents living in the high vs. low factory-density areas, and to examine the relations to gender and age. A total of 660 residents who had not moved within the 5 years preceding the study were sampled according to the stratified random sampling approach, at ages 35-44, 45-54,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Changhua residents living in high‐pollution areas had high levels of chromium (blood) and nickel (urine). These concentrations were markedly higher compared to previously reported data from people living in Western countries . Soil‐based heavy metal concentrations in Changhua were also high compared to other Taiwanese cities .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Changhua residents living in high‐pollution areas had high levels of chromium (blood) and nickel (urine). These concentrations were markedly higher compared to previously reported data from people living in Western countries . Soil‐based heavy metal concentrations in Changhua were also high compared to other Taiwanese cities .…”
Section: Discussioncontrasting
confidence: 76%
“…This work demonstrated an association between the concentrations of soil‐based heavy metals and CKD progression. The high levels of heavy metals in blood and urine were previously reported . However, it is unknown if soil‐based heavy metal concentrations directly increase bodily heavy metal concentrations, or if the soil, like a living entity, was only a container where environmental heavy metals accumulated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chromium and Ni are widely used industrial chemicals, and sufficient evidence exists that Cr and Ni compounds pose a carcinogenic risk to humans. Previous investigations revealed that the whole blood (B-Cr) and urinary Ni (U-Ni) levels of Cr of local residents living in the factory-dense areas of Changhua County were higher than those in other areas [39,40]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous researches have uncovered a critical association between the abnormally high incidence or mortality rates for common types of cancer and the high content of soil heavy metals in the specified regions. Moreover, some epidemiological studies also have suggested that exposure to high levels of specific heavy metals in environmental media may be responsible for the high levels of that in human blood, urine and hair Chang, Wang, Huang et al, 2006;Chiang et al, 2010;Rosas et al, 1989). More recently a case-control study on oral cancer and non-oral cancer patients living in central Taiwan has found that oral cancer patients' blood levels of heavy metal Cr, Ni, Cu and Zn were statistically significantly higher than those of non-oral cancer patients ; furthermore, these heavy metals are the same with the major components of PC1 influencing heavy metal pollution in Taiwan soil, which further indicates a tight link between heavy metal pollution in the environment and oral cancer.…”
Section: Resultsmentioning
confidence: 99%